Social attitudes and economic development: an epidemiological approach - Yann Algan; Pierre Cahuc (Institute for the Study of Labor (IZA), 2007)
In this paper we develop a new empirical approach to uncovering the impact of social attitudes on economic development. We first show that trust of second-generation Americans is significantly influenced by the country of origin of their forebears. In the spirit of the epidemiology literature, we interpret this phenomenon as the consequence of inherited social attitudes. We show that trust inherited by second-generation Americans from their country of origins has changed over time. This result allows us to use the inherited trust of second-generation Americans as a time-varying instrument to track back the evolution of trust in the home country of their parents. This strategy enables us to identify the specific impact of inherited trust on economic development relative to other traditional candidates, such as institutions and geography, by controlling for country fixed effects. We find that inherited trust has explained a substantial share of economic development on a sample of 30 countries during the post-war period, by improving total factor productivity and the accumulation of human and physical capital.
Keywords: 330; Soziale Werte; Social Capital; Vertrauen; Wirtschaftswachstum; Einwanderung; Generationenbeziehungen; USA